Associations of recreational and non-recreational physical activity with coronary artery calcium density vs. volume and cardiovascular disease events: the Multi-Ethnic Study of Atherosclerosis. (31st October 2019) - Thomas, Isac C; Takemoto, Michelle L; Forbang, Nketi I; Larsen, Britta A; Michos, Erin D; McClelland, Robyn L; Allison, Matthew A; Budoff, Matthew J; Criqui, Michael H
Abstract: Aims : The benefits of physical activity (PA) on cardiovascular disease (CVD) are well known. However, studies suggest PA is associated with coronary artery calcium (CAC), a subclinical marker of CVD. In this study, we evaluated the associations of self-reported recreational and non-recreational PA with CAC composition and incident CVD events. Prior studies suggest high CAC density may be protective for CVD events. Methods and results : We evaluated 3393 participants of the Multi-Ethnic Study of Atherosclerosis with prevalent CAC. After adjusting for demographics, the highest quintile of recreational PA was associated with 0.07 (95% confidence interval 0.01–0.13) units greater CAC density but was not associated with CAC volume. In contrast, the highest quintile of non-recreational PA was associated with 0.08 (0.02–0.14) units lower CAC density and a trend toward 0.13 (−0.01 to 0.27) log-units higher CAC volume. There were 520 CVD events over a 13.7-year median follow-up. Recreational PA was associated with lower CVD risk (hazard ratio 0.88, 0.79–0.98, per standard deviation), with an effect size that was not changed with adjustment for CAC composition or across levels of prevalent CAC. Conclusion : Recreational PA may be associated with a higher density but not a higher volume of CAC. Non-recreational PA may be associated with lower CAC density, suggesting these forms of PA may not have equivalent associations with this subclinical marker of CVD. While PA may affect the composition of CAC, the associations of PA with CVD risk appear to be independent of CAC.